Stand, Auswirkungen und Aufgaben der chilenischen Agrarreform. Beobachtungen in der nördlichen Längssenke Mittelchiles - Rother, Klaus (ERDKUNDE, 1973)
This paper, based on fieldwork in 1972, describes the characteristics and position of the reform programme in Chile and stresses the typical differences between the terms of office of the Frei and Allende governments. The author then investigates the effects of legislative measures on the rural landscape of the northern Valle Longitudinal of central Chile and concludes that: 1) the ownership and field patterns have largely survived the introduction of communal ownership, 2) the co-operative principle is dominant in farm operation. In many co-operatives there are clear tendencies to de marcation of individually used plots in order to work independently and profitably, 3) land use has become more intensified regionally than was the case before reform, but stock farming has stagnated, 4) division in the social structure of rural areas have become deeper, 5) scattered settlement and small hamlets have become denser. In conclusion, the future tasks of Chile in relation to the overall situation in the country are discussed